Clinical-histopathological correlation in acute appendicitis - Santiago, Pablo; Barberousse, Carlos (Cirugía del Uruguay, 1998)
A study of 48 patients operated with clinic diagnosis of acute appendicitis was done. lt took place in Emergency Service of Hospital Maciel in Montevideo, during a period of six month (ju/y-december 1996).